2020
DOI: 10.1007/s11250-020-02324-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the addition of Enterolobium cyclocarpum pods and Gliricidia sepium forage to Brachiaria brizantha on dry matter degradation, volatile fatty acid concentration, and in vitro methane production

Abstract: Effect of the addition of Enterolobium cyclocarpum pods and Gliricidia sepium forage to Brachiaria brizantha on dry matter degradation, volatile fatty acid concentration, and in vitro methane productionThe Alliance of Bioversity International and the International Center for Tropical Agriculture believes that open access contributes to its mission of reducing hunger and poverty, and improving human nutrition in the tropics through research aimed at increasing the eco-efficiency of agriculture.The Alliance is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 50 publications
2
11
0
5
Order By: Relevance
“…This is explained by the nutritional quality of the forages, especially by the structural carbohydrate content, e.g., the diets that included P. aculeata presented a higher NDF content that will trigger a lower gas production. This observation agrees with authors such as Sánchez et al [47] and Molina-Botero et al [48].…”
Section: Dry Matter Degradability In Vitro Gas Production and Phsupporting
confidence: 94%
“…This is explained by the nutritional quality of the forages, especially by the structural carbohydrate content, e.g., the diets that included P. aculeata presented a higher NDF content that will trigger a lower gas production. This observation agrees with authors such as Sánchez et al [47] and Molina-Botero et al [48].…”
Section: Dry Matter Degradability In Vitro Gas Production and Phsupporting
confidence: 94%
“…Blümmel et al (1997) suggested that a feed consisting of a mix of different kinds of ingredients can result in asynchrony in releasing nutrients, thus changing both the biomass of microorganisms produced and gas produced by them. In addition, one factor that can affect the fermentation and gas production of feeds is the configuration of their cell wall polysaccharides (Molina-Botero et al, 2020, Valencia-Salazar et al, 2021. Therefore, the digestibility values depend upon their composition of structural carbohydrates, including the concentration of lignin (Barahona and Sánchez, 2005) and FIGURE 1 | Modeled mean accumulated gas production (mL g −1 OM) for UHC, CB, LD, and 6 dietary mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Enteric CH 4 emission rates are associated with the physicochemical characteristics of the diet (e.g., CP and NDF contents), which have a direct impact on diet intake (Gaviria-Uribe et al, 2020) and eating frequency (Grant et al, 2015). Several studies have evaluated the effect of adding a legume to a grass on CH 4 production both in vitro (Tope et al, 2013;Molina-Botero et al, 2020) and in vivo (Molina-Botero et al, 2019a,b;Gaviria-Uribe et al, 2020;Montoya-Flores et al, 2020). Nevertheless, the conclusions drawn from these studies are unclear, as in some cases the addition of a legume increased in vitro CH 4 production (Carulla et al, 2005;Molina-Botero et al, 2020), but in others, it had the opposite effect (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, and for several forage species, including Kikuyu grass, the sward height is proposed as an easy-to-use grazing management criterion and a key performance predictor (Marin et al, 2017;de Souza Filho et al, 2019;Kunrath et al, 2020), as there is a strong relationship with the quantity and quality of the herbage that animals ingest. On the other hand, in vitro studies may predict enteric CH 4 production with reasonable accuracy and precision (Danielsson et al, 2017) and can help to identify promising strategies for in vivo studies oriented to reduce the environmental impact of livestock (Danielsson et al, 2017;Valencia Echavarria et al, 2019;Molina-Botero et al, 2020). Previous studies examined the effects of stage of regrowth on the nutritive value of whole plants of Kikuyu pastures and on the in vitro fermentation parameters (Ramírez et al, 2015;Vargas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%